Applying The Cooperative Learning Model Type of Teams Games Tournaments (TGT) to Increase Mathematics Learning Outcomes for Class VIII Students of s. Islamiah Hessa Air Genting year 2019/2020 - Herawati, Endang Luli (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
The purpose of this study was to determine learning outcomes using the TGT type cooperative learning model in mathematics. This research was conducted at SMP S Islamiyah Hessa Air Genting, Air Batu District, Asahan Regency. This research was conducted in Semester II of the 2019/2020 Academic Year, which is March – April 2020. The subjects in this study were students of class VIII-A SMP S Islamiyah Hessa Air Genting with a total of 32 people. The method used in this research is Classroom Action Research (CAR).Through the application of the TGT type learning method, it can improve students' mathematics learning outcomes in class VIII-A SMP S Islamiyah Hessa Air Genting for the 2019/2020 academic year. This can be seen from the results of the final study test, there are 25 students who complete or 75%. But the activities in the first cycle have not been said to be successful because they have not met the classical completeness of 85% so that it needs to be repeated so that students' ability to study the material independently and discuss with their original group through the TGT type cooperative learning model can be improved, it is necessary to carry out improvements in carrying out actions classroom learning. For this reason, it was carried out in cycle II. The implementation in cycle II went better and more conducive. This can be seen from the results of the final study test, there are 28 students who complete or 87.5%. So by applying the Teams Games Tournaments (TGT) type cooperative learning model in class VIII of SMP S Islamiyah Hessa Air Genting for the 2019/2020 academic year, it can improve mathematics learning outcomes.